Pendampingan Pengembangan Sumber Daya Manusia dan Model Bisnis Social Enterprise Lingkar Organik - Tegar Satya Putra; Agnes Gracia Quita; Mayasari, Agatha (Jurnal Atma Inovasia, 2022)
Social enterprise is a typical organization in the social economy. Social enterprise has two purposes: meeting the principle of proﬁt maximization and addressing social and environmental purposes, which includes reinvesting in the community. These two purposes are aimed to be fulﬁlled simultaneously, as social enterprises seek to balance activities that provide economic benefits with social goals. Lingkar Organik is a social company located in Yogyakarta that continues to grow and develop. To develop a business entity, growth in organizational performance is needed, both in terms of financial performance and service quality. Employees in social companies come from various cultural backgrounds, education, social conditions, and generational gaps become a significant challenge in managing human resources to explore their talents. Another challenge is the lack of understanding of the social vision and objectives that are the main foundation. Therefore, it is important to have employee development and internal branding for Lingkar Organik.